Buto, Ägypten. Aktuelle Arbeiten und Ausblicke. Die Arbeiten in den Jahren 2019 und 2020 - Hartmann, Rita; Jeuthe, Clara; Konert, Sarah-Mercedes (e-Forschungsberichte des DAI, 2021)
Future research for the settlement site of Buto in the western Delta/Egypt is planned to focus on the settlement development during the Old Kingdom Period (ca. 2700–2200 BC), although corresponding field work cannot yet begin at this point. Nevertheless, preliminary work is under way, including various projects for the analysis and publication of the results obtained so far, especially of the Early Dynastic Period (ca. 3200–2700 BC) but also of the Third Intermediate and Late Period structures in Buto (ca. 950–525 BC).